Mechanism studies on the superior optical limiting observed in graphene oxide covalently functionalized with upconversion NaYF4:Yb3+/Er3+ nanoparticles - He, Tingchao (2013)
Superior optical limiting (OL) characteristics and mechanisms are explored in a novel nanocomposite made from graphene oxide (GO) and NaYF4:Yb3+/Er3+ nanoparticles via covalent chemical bonding. Due to the synergistic effect of enhanced nonlinear scattering, two-photon absorption, and efficient energy transfer between NaYF4:Yb3+/Er3+ nanoparticles and GO, the nanocomposite displays dramatically improved OL effects compared to either GO or NaYF4:Yb3+/Er3+ nanoparticles, making it a very promising material for practical OL devices.